En ook gehoor? Vrae rondom die gereformeerde siening van die kerk - Smit, DJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
'And heard'? - Questions concerning Reformed ecclesiology" The essay honours the legacy of W.D (Willie) Jonker by reflecting on some theological assumptions in his own theology motivating his concern that the church of Jesus Christ should continuously experience spiritual renewal and practice concrete and visible discipleship in order to proclaim the gospel with some credibility and conviction in an increasingly secularized world – a concern again expressed in his study on the relevance of the church that has recently been published for the first time. The essay argues that these assumptions have all been characteristic of the Reformed tradition, since Calvin. It points out that Calvin already held similar views regarding the church, and then demonstrates the crucial importance of several of these typical Reformed convictions in Jonker’s own theological work, over several decades. It discusses the central place in Reformed ecclesiology of confessions of faith, of the visible form and order of the church, and of the life, witness and service of the church. It argues that – for Calvin, the Reformed tradition, and Jonker – these three ecclesiological aspects are of central importance, and that the contribution of Reformed ecclesiology to contemporary ecumenical endeavours also depends on these emphases.